Development of Nurse Behavior Models Based on Work Productivity and the Informational Motivation Behavioral Skill on Compliance with Documenting Integrated Patient Progress Record - Rochman, Diana; Triharini, Mira; Indarwati, Retno; Ayatulloh, Daviq; Priyantini, Diah (Indonesian Journal of Global Health Research, 2024)
Integrated patient progress record (IPPR) documentation shows that it is still not 100% complete and needs improvement. The aim of the research is to develop a model of nurse behavior based on work productivity and the informational motivation behavioral skills on IPPR documentation compliance. Phase 1 research used explanatory research with a cross sectional approach on 155 nurses at Blambangan Hospital, Banyuwangi who were recruited using cluster random sampling. Independent variables: organizational characteristics, nurse characteristics, work characteristics, information skills, social motivation, documentation behavior and the dependent variable is documentation compliance. The instrument is an instrument that was modified by the researcher and has first been tested and declared valid and reliable. Analysis of research data using SEM-PLS. Phase 2 research uses a qualitative design in the preparation of modules through FGD and expert consultation. Phase 1 research shows that the outer model construct validity of all indicators is valid with loading factor values ≥ 0.5. Reliability for all indicators shows reliability with Cronbach's alpha > 0.6. Hypothesis testing showed that all were significant, only the influence of work characteristics on nurse characteristics was not significant. The results of the phase 2 research module are based on recommendations from FGDs and expert consultations. During model development, the strongest path in combining the two theories is the nurse characteristics path through the work productivity and IMBS-based documentation behavior path and towards IPPR documentation compliance. So, it is very important to emphasize that in increasing nurses' compliance in carrying out IPPR nursing documentation, it is necessary to improve nurses' self-efficacy by increasing the knowledge, abilities, attitudes, personality, self-perception, beliefs and hopes that exist within nurses.